Il legame tra lo spazio e l’individuo in Petrarca e Leopardi - Dabasi, Julia (Italianistica Debreceniensis, 2017)
The interdisciplinary approach in history makes it possible to widen researchers’ perspectives. Italian literature is one medium in which we can reflect the relationship between geography, identity and imagination. John Agnew’s idea that ‘Place is a meaningful site that combines location, locale and sense of place’ conveys the main aspect of a ‘meaningful location’ and gives us a framework within which we can rethink space and place through Italian literature.1 In my research, I intend to examine the connections between identity and landscape, how experiences form the view of the environment through Giacomo Leopardi’s Infinity (1819) and Francis Petrarch’s letter of 26, April, 1336 in which he describes a vision about his ascent up Mount Ventoux. My main aim is to present how the impressiveness of nature becomes visible through the experiences of Leopardi and Petrarch, which is part of their existence. The mountain and the sea are key elements of these texts. The two places chosen and described by the poets have different significance: while Petrarch considered that the Mount Ventoux is the place of spiritual fulfilment, for Leopardi the hill of Recanati meant an isolated place where he could let his imagination roam free. All in all, this research offers new perspective to discover relationship between Italian literature and other disciplines in order to answer other, complex theoretical questions. I examined the topic from an interdisciplinary view to highlight the ways in which history, geography and literature can be linked.